Use of generalized hypergeometric functions in analytic stellar models (1989)
The present paper deals with the technique of integration theory of special functions applied to two simple analytic stellar models. We consider two cases, one with a non-linear dependence of the radial density and the other with a generalized energy generation rate. The integration theory of the generalized hypergeometric functions is applied to evaluate analitically the rate of nuclear energy generation. Some known results follow as particular cases of our formulae established here.